Status of Scheduled Tribe Students in Science, Technology, Engineering and Mathematics (STEM) at the Level of Higher Education in India - Ankur Nandi; Tarini Halder; Tapash Das (Advanced Journal of STEM Education, 2024)
STEM fields play a pivotal role in driving innovation and economic growth. Ensuring equitable access for all students, including those from disadvantaged backgrounds, is crucial for fostering diversity and inclusivity. This study examines the enrollment status of Scheduled Tribe (ST) students in Science, Technology, and Engineering at higher education levels in India, focusing on their participation in STEM fields. This study explores the barriers that ST students face in accessing and persisting in STEM education and provides suggestions to enhance their participation and success. This study is qualitative and documentary in nature. All-India Survey on Higher Education Reports AISHE reports (2011-12 to 2021-22), Department of Higher Education, Ministry of Education, Govt. of India. The study revealed that in Bachelor of Science (B.Sc.) programs, male ST student enrollment was higher than females from 2011-2012 to 2018-2019, but this trend reversed from 2018-2019 to 2021-2022, with female enrollment surpassing males. Similarly, in Master of Science (M.Sc.) programs, male enrollment was higher until 2013-2014, after which female enrollment exceeded males from 2014-2015 to 2021-2022. However, in the engineering and technology fields (B.E., M.E., B.Tech., M.Tech.), male students consistently maintained higher enrollment rates than female students at both undergraduate and postgraduate levels.